2016
DOI: 10.1111/ceo.12691
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical results of posterior chamber phakic intraocular lens implantation to correct myopia

Abstract: Background: The aim of this study was to determine whether implantable collamer lens (ICL) implantation to correct myopia is an effective and safe surgical option even after long-term follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 38 publications
(38 reference statements)
5
46
1
1
Order By: Relevance
“…In this study, similar to other phakic IOL implantation series in the literature, the expected increase in UDVA after the Eyecryl phakic IOL implantation was observed (5,8). The safety index in this study was >1.0, indicating that the mean patient CDVA had increased after the operation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, similar to other phakic IOL implantation series in the literature, the expected increase in UDVA after the Eyecryl phakic IOL implantation was observed (5,8). The safety index in this study was >1.0, indicating that the mean patient CDVA had increased after the operation.…”
Section: Discussionsupporting
confidence: 87%
“…They reported that the regression between the first and third years was statistically significant. Lee et al (5) reported that the mean SE had decreased to -0.58±0.72 D in patients with a follow-up period of at least 5 years and 69.8% of the patients were within ±0.50 D. Guber et al (16) reported a safety index of 1.25±0.57 at the 10-year followup with an average SE of 0.7 D. Moya et al (15) stated that the SE was -1.77±1.93 D in the last examination of 144 patients after 12 years of follow-up. The relatively good refractive outcomes in the early period and the high efficacy index in the long run, despite myopic shifts, are common points in all of these studies and in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the optical quality of the eye decreases with aging [27] . In our research, the average age of the subjects was 39.16 ± 7.52, older than previously reported subjects [28,29] . We postulated that the crystal density increases with age, and the intraocular scattering index also increases.…”
Section: Discussioncontrasting
confidence: 57%
“…In a report of 3-year follow-up of 526 eyes of 294 patients with mean preoperative MRSE of −10.06±3.74 D participating in the US FDA clinical trial of the ICL, 59.3% had 20/20 or better uncorrected visual acuity (UCVA), and 94.7% had 20/40 or better UCVA if best-corrected visual acuity was 20/20 and they were targeted for emmetropia; 67.5% of patients were within 0.5 D and 88.2% were within 1.0 D of predicted refraction. 4 Lee et al 12 reported 281 eyes of 145 patients who were followed for at least 5 years (mean =87±18.9 months) and had mean preoperative MRSE of −8.74±2.27 D (−4.00 to −15.25 D). They noted 60.5% UCVA 20/20 or better: At the end of follow up, the postoperative logMAR uncorrected distance visual acuity (UDVA) was 0.30 (approximately 6/12) or better in 254 eyes (90.4%), 0.10 (approximately 6/7.5) or better in 238 eyes (84.7%) and 0.00 (6/6) or better in 170 eyes (60.5%).…”
Section: Effectiveness: Refractive Outcomesmentioning
confidence: 99%